Menuju Kebijakan Pendidikan Satu Atap: Kritik atas Dualisme dan Dikotomi Pendidikan di Indonesia - Siti Khoiriyah; Amiruddin Amiruddin; Mohammad Salik; Achmad Zaini (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
Politics and two-roof education policies in the regulation of Indonesia's national education system still need to improve at the level of implementation. Several two-roof education policies tend to be contradictory, such as the instructions and technical implementation of Graduate Competency Standards (SKL) at every level of education and subjects, the qualifications for the distance to the establishment of educational institutions, and regulations on accepting new students. This article aims to examine the rules and policies of two-roof education critically. The method used in this research was a literature study. There were three results of the critical analysis of this research. First, there was no policy regulation on the Graduate Competency Standard (SKL) measurement scale, so a policy regulation is needed on the SKL measuring instrument. Second, there were no more general and humanist current regulations and policies regarding the qualifications for the distance to the establishment of educational institutions, so a policy for the distance for the establishment of schools and madrasahs is needed that is in line with the needs and goals of national education. Third, review the technical implementation of accepting new students.